2020
DOI: 10.3390/en13030566
|View full text |Cite
|
Sign up to set email alerts
|

Effect of EGR and Fuel Injection Strategies on the Heavy-Duty Diesel Engine Emission Performance under Transient Operation

Abstract: To reduce the smoke and nitrogen oxide (NOx) emissions; a detailed study concerned with exhaust gas recirculation (EGR) and diesel injection strategy was conducted on a two-stage series turbocharging diesel engine under transient operating condition. One transient process based on the constant speed of 1650 r/min and load increases linearly from 10% to 100% within 5 s was tested in this study. The effect of the EGR valve control strategy on engine transient performance was examined. The results show that bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…The results show that the best compromise emission can be obtained by closing the EGR valve at 1.5 s and opening it at 4 s through open-loop control. When the exhaust oxygen concentration is controlled as a closed-loop target, although the EGR opening curve similar to the open-loop control obtained, the emission will deteriorate due to the delay of closed-loop control [23].…”
Section: Introductionmentioning
confidence: 59%
“…The results show that the best compromise emission can be obtained by closing the EGR valve at 1.5 s and opening it at 4 s through open-loop control. When the exhaust oxygen concentration is controlled as a closed-loop target, although the EGR opening curve similar to the open-loop control obtained, the emission will deteriorate due to the delay of closed-loop control [23].…”
Section: Introductionmentioning
confidence: 59%
“…The EGR rate in the study is calculated by measuring the volumetric fraction of CO 2 in the intake and exhaust gases using the Cambustion NDIR500. The calculation method is presented in Equation (5) [22]:…”
Section: Data Processingmentioning
confidence: 99%
“…Pennington et al [21] studied the torque increase transient process lasting from 2 to 10 s. By reducing the variable geometry turbocharger (VGT) opening and EGR valve opening, they minimized turbocharger lag, resulting in reduced fuel consumption and particulate matter emissions. Zhang et al [22] studied a 5 s transient process on a two-stage turbocharged diesel engine. They found that closing the EGR valve at 1.5 s and reopening it at 4 s through open-loop control achieved optimal compromise emissions.…”
Section: Introductionmentioning
confidence: 99%